A cure for HIV: is it in sight?. Issue 7 (July 2014) - Pace, Matthew; Frater, John
Abstract : HIV is a devastating disease affecting millions of people worldwide despite the advent of successful antiretroviral therapy (ART). However, ART does not result in a cure and has to be taken for life. Accordingly, researchers are turning towards cure efforts, particularly in the light of two patients whose HIV has been seemingly eradicated. Numerous approaches and strategies have been considered for curing HIV, but no scalable and safe solution has yet been reached. With newly discovered difficulties in measuring the HIV reservoir, the main barrier to a cure, the only true test of cure is to stop ART and see whether the virus becomes detectable. However, it is possible that this treatment interruption may be associated with certain risks for patients. Here, we compare the current major approaches and recent advances for curing HIV, as well as discuss ways of evaluating HIV cure and the safety concerns involved.